2022
DOI: 10.1111/hel.12940
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple therapy with vonoprazan 20 mg daily as a first‐line treatment for Helicobacter pylori infection: A single‐center, open‐label, noninferiority, randomized controlled trial

Abstract: Background Although vonoprazan has been proven to be a highly potent drug for Helicobacter pylori eradication, there have been no randomized trials comparing the effectiveness of regimens containing vonoprazan 20 mg daily with alternative standard strategies. We aimed to assess the efficacy, tolerance, and cost‐effectiveness of quadruple therapy with vonoprazan 20 mg daily as a first‐line therapy for H. pylori eradication. Materials and Methods We conducted a single‐center, open‐label, noninferiority, randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 37 publications
(77 reference statements)
2
24
0
Order By: Relevance
“…7,8 Vonoprazan was used in VBAF to replace PPI to improve the eradication rate. Recent clinical trials [30][31][32] focusing on vonoprazancontaining quadruple therapy proved its high efficacy for eradicating H. pylori in China. Among the 3 studies, furazolidone-containing vonoprazan quadruple therapy showed the highest eradication rate (97.4% in PP analysis), which was similar with the eradication rate achieved by our study (97.7% in PP analysis).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Vonoprazan was used in VBAF to replace PPI to improve the eradication rate. Recent clinical trials [30][31][32] focusing on vonoprazancontaining quadruple therapy proved its high efficacy for eradicating H. pylori in China. Among the 3 studies, furazolidone-containing vonoprazan quadruple therapy showed the highest eradication rate (97.4% in PP analysis), which was similar with the eradication rate achieved by our study (97.7% in PP analysis).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 MNZ is approved as second-line treatment in Japan in combination with VPZ and amoxicillin and Murakami et al 16 Bismuth-containing quadruple therapy has been recommended as the first-line treatment of H. pylori infection in regions with high resistance rate of clarithromycin. 20 Lu et al 21 assessed the efficacy of 10-and 14-day VPZ-containing bismuth amoxicillin, furazolidone quadruple therapy (amoxicillin 1 g bid and furazolidone 100 mg bid) in China. A total of 156 patients were included and randomized to receive the VPZ quadruple therapy, both groups showed high efficacy with eradication rates of 10-and 14-day VPZ-containing quadruple therapy of 98.6% and 97.4% PP.…”
Section: Discussionmentioning
confidence: 99%
“…The publications, total citations, and H-index of the 10 most productive countries were analyzed in Table S2. Japan had the largest number of publications (45), H-index (21), and citations (1, 143), followed by China with 7 publications. Japan was the region where VPZ-based H. pylori eradication regimens were most widely used, followed by China and the United States.…”
Section: Analysis Of Countriesmentioning
confidence: 99%
“…Endpoint 1 focused on the H. pylori eradication rate assessed through a 13 C urea breath test ( 13 C‐UBT), 27 conducted 4 weeks after the treatment. Subjects refrained from taking PPIs or P‐cab 2 weeks before the test, and any antibiotics 4 weeks prior.…”
Section: Methodsmentioning
confidence: 99%
“…Comprehensive data, encompassing age, sex, body mass index (BMI), and history of smoking and drinking were harvested from all patients. Endpoint 1 focused on the H. pylori eradication rate assessed through a 13 C urea breath test ( 13 C-UBT), 27 conducted 4 weeks after the treatment. Subjects refrained from taking PPIs or P-cab 2 weeks before the test, and any antibiotics 4 weeks prior.…”
Section: Data Collection and Observation Indicatorsmentioning
confidence: 99%